La diplomazia sportiva dell’Azerbaigian e le relazioni con l’Unione Europea - Rahiminia, Dariush (Eracle. Journal of Sport and Social Sciences, 2024)
This paper focuses on the particular socio-political dynamics of the sports world in the Republic of Azerbaijan, which participates in European competitions despite it is geographically located in Asia. Specific attention is paid to the influence of the mega-events on the relationships with the European Union. Azerbaijan is a transcontinental and multicultural country. In recent years, it has strategically developed sports infrastructure for diplomatic purposes. Drawing on the concept of "sports diplomacy", and by analyzing official statements and interviews, the article aims to delve into the historical context of Azerbaijan's integration into the European sport field. The fundamental stages of this process are detected, raising the attention on an area that is still underexplored. In particular, the paper explores the role played by sport mega-events against the backdrop of international politics, on the one hand, but also of the country's internal political organization, on the other.